Economic Transformation and Poverty Challenges on Sulawesi Island: Base Sector Panel Analysis and Regional Classification - Ihsan Ashari (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research examines the relationship between poverty levels, population growth, and regional potential across six Sulawesi provinces from 2015 to 2025. Poverty remains a significant challenge, with variations influenced by dependence on primary sectors like agriculture and mining, coupled with high population growth rates. Using panel data analysis with the Fixed Effect Model (FEM), the study finds that population growth significantly increases poverty levels, with a coefficient of 0.324 (p<0.05). This suggests that unchecked population growth exacerbates poverty if not accompanied by effective control and job creation. Conversely, regional potential, measured through leading sectors (LQ>1), significantly reduces poverty, with a coefficient of -0.456 (p<0.01). Provinces with strong leading sectors experience faster poverty reduction, highlighting the importance of optimizing these sectors. To address poverty, integrated family planning programs and the development of leading sectors should be prioritized. These strategies align with the Sustainable Development Goals (SDGs), particularly Goal 1: No Poverty. The findings offer valuable insights for policymakers and regional development strategies to achieve sustainable poverty reduction in Sulawesi